Mitigation strategy on reduction greenhouse gas (GHG) emission of landuse sector for the province of Papua - Elvis Franklin Suebu; Joni Hermana; Rachmat Boedisantoso (Center for Science and Technology, IAIN Surakarta, 2017)
Studying the right strategy for implementing mitigation measures to reduce GHG emissions in an effort to control climate change caused by deforestation and forest degradation (REDD+) in Papua Province is a crucial step that must be taken. In 2010, emission levels in Papua Province were dominated by the forestry sub-sector and other land use, amounting to 639,818,463 tons of CO2eq, which accounted for approximately 99.8% of the total GHG emissions of 640,737,952.64 tons of CO2eq. To analyze the implementation strategy of REDD+ mitigation, the calculation of carbon emission levels must first be conducted. Carbon emission calculations for this sub-sector follow the methodology developed by the IPCC GL-2006. Meanwhile, for the forestry and other land use sub-sectors, both historical and forward-looking approaches were used. The carbon emissions level from the forestry sub-sector was estimated at 921,779,031.23 tons of CO2eq using the historical method and 1,052,683,205.46 tons of CO2eq using the forward-looking method for the mitigation program at the end of 2020. The mitigation strategy focused on carbon uptake and carbon storage stabilization. The mitigation scenario for the forestry sub-sector was capable of reducing emissions by 552,303,873 tons of CO2eq, equivalent to 52.47% of the total cumulative emissions at the end of 2020, based on the forward-looking method.